Salib di Ujung Timur Nusa Lease: Gereja Ebenhaezer, Tinggalan Kolonial di Desa Sila Leinitu Kecamatan Nusalaut - Andrew Huwae (Balai Arkeologi Maluku, 2013)
Not many churches in Indonesia, which still retain the authenticity of nature since the church was founded. Despite being the oldest church in Ambon Islands Lease, Ebenhaezer Church in the village of Sila Leinitu Nusa Laut sub-district which was built in 1715, is one of the many churches in the Moluccas which still retains the authenticity of nature, even after repeated experience of building renovations. This research aims to describe the architecture and layout of the church. In addition, this paper describes the findings of worship fixtures in the church hall which is now very rare in other churches in the Moluccas.Tidak banyak gereja di Indonesia yang masih mempertahankan sifat keaslian sejak gereja tersebut didirikan. Meskipun menjadi gereja tertua di Kepulauan Ambon Lease, Gereja Ebenhaezer di desa Sila Leinitu kecamatan Nusa Laut yang dibangun pada tahun 1715, adalah salah satu dari sekian banyak gereja di Maluku yang masih mempertahankan sifat keaslian tersebut, walau telah beberapa kali mengalami renovasi bangunan. Penulisan ini bertujuan untuk menggambarkan teknik arsitektur dan tata ruang gereja. Selain itu juga, penulisan ini menjelaskan tentang hasil temuan perlengkapan peribadatan di dalam ruang gereja yang kini sudah sangat jarang ditemui pada gereja lainnya di Maluku.